Intravenous Tissue Plasminogen Activator in Combination With Mechanical Thrombectomy: Clot Migration, Intracranial Bleeding, and the Impact of “Drip and Ship” on Effectiveness and Outcomes - Chang, Adam; Beheshtian, Elham; Llinas, Edward J.; Idowu, Oluwatoyin R.; Marsh, Elisabeth B. (Frontiers in Neurology, 2020)
Purpose: Intravenous tissue plasminogen activator (tPA) is indicated prior to mechanical thrombectomy (MT) to treat large vessel occlusion (LVO). However, administration takes time, and rates of clot migration complicating successful retrieval and hemorrhagic transformation may be higher. Given time-to-effectiveness, the benefit of tPA may vary significantly based on whether administration occurs at a thrombectomy-capable center or transferring hospital. Methods: We prospectively evaluated 170 individuals with LVO involving the anterior circulation who underwent MT at our Comprehensive Stroke Center over a 3.5 year period. Two thirds (n= 114) of patients were admitted through our Emergency Department (ED). The other 33% were transferred from outside hospitals (OSH). Patients meeting criteria were bridged with IV tPA; the others were treated with MT alone. Clot migration, recanalization times, TICI scores, and hemorrhage rates were compared for those bridged versus treated with MT alone, along with modified Rankin scores (mRS) at discharge and 90-day follow-up. Multivariable regression was used to determine the relationship between site of presentation and effect of tPA on outcomes. Results: Patients presenting to an OSH had longer mean discovery to puncture/recanalization times, but were actually more likely to receive IV tPA prior to MT (70 versus 42%). The rate of clot migration was low (11%) and similar between groups, though slightly higher for those receiving IV tPA. There was no difference in symptomatic ICH rate after tPA. TICI scores were also not significantly different; however, more patients achieved TICI 2b or higher reperfusion (83% versus 67%, p=0.027) after tPA, and TICI 0 reperfusion was seen almost exclusively in patients who were not treated with tPA. Those bridged at an OSH required fewer passes before successful recanalization (2.4 versus 1.6, p=0.037). Overall, mean mRS scores on discharge and at 90 days were significantly better for those receiving IV tPA (3.9 versus 4.6, 3.4 versus 4.4 respectively, p~0.01) and differences persisted when comparing only patients recanalized in under 6 hours. Conclusion: Independent of site of presentation, IV tPA before MT appears to lead to better radiographic outcomes, without increased rates of clot migration or higher intracranial hemorrhage risk, and overall better functional outcomes.